3D Strain helps relating LV function to LV and structure in athletes - Stefani, Laura (BioMed Central, 2014)
INTRODUCTION: The evaluation of cardiac contraction could benefit from a connection with the underlying helical structure of cardiac fibers in athletes either completely healthy or with minor common cardiopathies like Bicuspid Aortic Valve (BAV). This study aims to exploit the potential role of 3D strain to improve the physiological understanding of LV function and modification due to physical activity as a comparative model. METHODS: Three age-matched groups of young (age 20.3 ± 5.4) individuals are prospectively enrolled: 15 normal healthy subjects, 15 healthy athletes, and 20 athletes with bicuspid aortic valve (BAV). All subjects underwent echocardiographic examination and both 2D and 3D strain analysis. RESULTS: All echo parameters were within the normal range in the three groups. Global values of end-systolic longitudinal and circumferential strain, assesses by either 2D or 3D analysis, were not significantly different. The 3D strain analysis was extended in terms of principal and secondary strain (PS, SS). Global PS was very similar, global SS was significantly higher in athletes and displays a modified time course. The comparative analysis of strain-lines pattern suggests that the enhancement of LV function is achieved by a more synchronous recruitment of both left- and right-handed helical fibers. CONCLUSIONS: 3D strain analysis allows a deeper physiological understanding of LV contraction in different types of athletes. Secondary strain, only available in 3D, identifies increase of performances due to physical activity; this appears to follow from the synergic activation of endocardial and epicardial fibers.